A Case for Raising the Camera: A Driving Simulator Test of Camera-Monitor Systems. (March 2023) - Bernhard, Christoph; Reinhard, René; Kleer, Michael; Hecht, Heiko
Objective: This experiment provides a first-of-its-kind driving-simulator study to investigate the feasibility of camera-monitor systems (CMS) with displaced side-mounted cameras in sedans. Background: Among the increasing number of studies investigating the replacement of side-mounted rearview mirrors with CMS, the placement of side-mounted cameras has been largely neglected. Moreover, user preferences with respect to camera placement have not been validated in a driving simulator. Past research merely has shown that the vertical camera position can affect distance perception. Method: In a driving simulator experiment, we investigated the effects of rearward camera placement on driver acceptance and performance. Thirty-six participants performed multiple lane changes in a last safe-gap paradigm. The camera position, ego-velocity, and velocity of the approaching vehicle varied across the experiment. Results: The results suggest a clear preference for a high rearward perspective, whereas participants disliked the lower viewpoint. However, these stark differences were only marginally mirrored in lane change performance. Average safety margins tended to decrease and their variation tended to increase for the low camera position. Conclusion: Even if the impact of the camera position on driving behavior seems to be small in sedans, driver expectations show clear-cut preferences. When designing CMS, this should be taken into account, as these preferences could promote the use of CMS and thus their positive impact on safety. Application: Designers should place side-mounted cameras as high as possible to increase acceptance of CMS. Low camera positions are not recommended, as they might decrease safety margins and are not appreciated by drivers.